An efficient [3+2] annulation for the asymmetric synthesis of densely-functionalized pyrrolidinones and γ-butenolides. Issue 76 (25th August 2020) - Qian, Hui; Sun, Song; Zhao, Wanxiang; Sun, Jianwei
Abstract : Disclosed here is a new [3+2] annulation of siloxy alkynes that provides robust access to highly enantioenriched, densely-substituted pyrrolidinones and γ-butenolides, whose direct synthesis remains challenging. Abstract : Disclosed here is a new [3+2] annulation of siloxy alkynes that provides robust access to highly enantioenriched, densely-substituted pyrrolidinones and γ-butenolides, whose direct synthesis remains challenging. This process also represents a rare asymmetric synthesis of enantrioenriched molecules from siloxy alkynes.